2017
DOI: 10.1080/21645515.2017.1409317
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary termination of pregnancy: An opportunity for Measles, Mumps and Rubella vaccination in an Italian healthcare local unit

Abstract: In Italy, the National Plan for the Elimination of Measles and Congenital Rubella 2010–15 suggests offering Measles, Mumps and Rubella (MMR) vaccination to susceptible women who underwent voluntary termination of pregnancy (VTP) In Rome, S. Eugenio Hospital is one of the structures where VTP is practised in an Operative Unit called “Family Planning” The primary goal of this study was to estimate the prevalence of susceptibility to rubella, using IgG and IgM immunoassays, among women accessing VTP and to offeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The achieved prevalence of rubella susceptibility in this study confirmed data of a recent meta-analysis (Pandolfi et al, 2017) showing that, at a global level, the proportion of rubella-susceptible childbearing women is still high. The higher susceptibility to rubella among women born in Italy confirmed previous Italian reports focused on wVTP (Pettinicchio et al, 2018) and continues to show a dramatically higher susceptibility rates when compared to women born in other European countries, especially if mEPP (Vilajeliu et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The achieved prevalence of rubella susceptibility in this study confirmed data of a recent meta-analysis (Pandolfi et al, 2017) showing that, at a global level, the proportion of rubella-susceptible childbearing women is still high. The higher susceptibility to rubella among women born in Italy confirmed previous Italian reports focused on wVTP (Pettinicchio et al, 2018) and continues to show a dramatically higher susceptibility rates when compared to women born in other European countries, especially if mEPP (Vilajeliu et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Voluntary termination of pregnancy (VTP), pre-conception and post-partum phases (Hisano et al, 2016), as well as Occupational Medicine assessments for healthcare workers were deemed to be opportunities for screening and vaccinating rubella seronegative women of childbearing potential. However, data about vaccination acceptance following these phases is rarely reported or considered suboptimal (Little et al, 2015; Pettinicchio et al, 2018; Santoro et al, 2016). In spite of implementation of several immunisation strategies, as in-hospital vaccination before discharge or active calls by public health services, anti-rubella vaccination rates following VTP in Italy have been considered worrying and widely unsatisfactory (Pettinicchio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission of measles virus from a pregnant woman to her fetus (congenital measles) has been reported in neonates born to women who had measles within 10 days of delivery 25,26 . Congenital measles is defined as presence of the rash at birth or VOLUME 18 ISSUE 2, APRIL-JUNE 2019…”
Section: Complicationsmentioning
confidence: 99%